Pengelolaan Evaluasi Pembelajaran Kurikulum 2013 Di SD Negeri Salatiga 06 - Ayu Bintari, Niken Armeda, Prof. Dr. Sutama, M.Pd, Dr. H. Samino, MM (2015)
This study aims to: (1) To describe the evaluation of learning management curriculum 2013 affective aspects in SD Negeri Salatiga 06. (2) Describing the evaluation of learning management curriculum 2013 on cognitive aspects in SD Negeri Salatiga 06. (3) Describe the evaluation of learning management curriculum 2013 psychomotor aspect SD Negeri Salatiga 06. This research use descriptive research, research design using qualitative descriptive method. Implementation of this research is in SD Negeri Salatiga 06. Time of the study was conducted over six months, since the month of September 2014 until the month of March 2015. The data used in this study are primary data and secondary data. Source of data obtained through interviews, observation and documentation. As an informant in this study were teachers and students of class IV SD Negeri Salatiga 06. The validity of the data used in this study is the triangulation method and the triangulation of sources. Data analysis techniques using interactive analysis (model interwoven), which consists of three components: data reduction, data presentation and conclusion. According to the data analysis and discussion, we concluded that: (1) Management of the evaluation of the affective aspects of learning curriculum 2013 in SD Negeri Salatiga 06 are teachers have to evaluate the affective aspects, especially the evaluation of attitudes and self-evaluation, while evaluation of affective aspects in evaluation activities between friends and journal notes the teacher at the beginning of the implementation of the curriculum in 2013 has been performed by teachers, but over time the evaluation between friends and journal notes the teacher is no longer made by the teacher. Teachers just made when the supervision will be conducted by the headmaster or supervisor. (2) Management evaluation of the cognitive aspects of learning curriculum 2013 in SD Negeri Salatiga 06 are teachers already perform well, in which the teacher in evaluating the cognitive aspects of evaluation include written, oral and assignment. Evaluation of cognitive aspects carried by teachers at each end of the meeting, so as to know the level of students' absorption of the material presented by the teacher. This type of evaluation assignment given by the teacher carried individually and in groups. (3) Management evaluation psychomotor aspects of learning curriculum 2013 in SD Negeri Salatiga 06 that teachers in evaluating psychomotor aspects already well integrated in accordance with the curriculum in 2013, where in evaluating aspects of the psychomotor type of assignment is considered that the evaluation of performance, project, and assessment. Type of assignment in the aspect of performance evaluation, project evaluation and assessment carried in groups, so that each group had to demonstrate the cohesiveness of the group.